OPTIMASI PENDAPATAN UMKM MELALUI PLATFORM DIGITAL MARKETING DUSUN MUNGKID, MAGELANG - Wibowo, Febrian Wahyu; Sujono, Rusny Istiqomah; Kamal, Al Haq; Salam, Abdul; Ismiati, Baiq; Yunadi, Ahmad; Layli, Meutia; Giansyah, Arifki (Universitas Mataram, 2024)
Technological advances encourage various types of elements of society, including the MSME business element. The convenience presented by technology influences the development of a business that initially only operated in the offline realm, but is now starting to move into the digital realm. This trend shift must of course be balanced by the ability and understanding of the community, especially MSMEs. One of the most important areas is marketing which has now shifted to using digital media with various conveniences offered, MSME players must follow these developments in order to be able to compete with other business actors. This activity was carried out with the aim of providing in-depth understanding and expertise to MSME players in the field of digital marketing and increasing MSME income through digital platforms. During the implementation of the event, several problems were discovered, such as a lack of public understanding about digital marketing, low motivation to run a business, young people's indifference to the MSME industry, difficulty in visual design creativity and uneven banking payments, these problems made the development of MSMEs not optimal. It is hoped that there will be a similar agenda to provide continuous training so that the MSME industry continues to grow.